Teaching ethics in organ transplantation and tissue donation - cases and movies - Schicktanz, Silke; Wiesemann, Claudia; Wöhlke, Sabine; Carmi, Amnon (Universitätsverlag Göttingen, 2010)
Organ transplantation is a thrilling new option for modern surgery giving hope for chronically ill patients, and, at the same time, stirring controversial ethical questions on human identity and the meaning of the human body. Being a global and transnational endeavor, organ transplantation raises universal ethical concerns and, yet, has to be adapted to culturally mediated believes. In this book, 30 case studies collected from all over the world illustrate the range of global and local, ethical, social, and cultural problems associated with this new form of treatment. Together with a list of relevant movies, the collection provides a unique resource for ethics education in medicine, health care, philosophy, and religious studies. The authors have completed the teaching material by a systematic introduction into the field of transplantation ethics.